2004
DOI: 10.1002/path.1593
|View full text |Cite
|
Sign up to set email alerts
|

Gastric B‐cell mucosa‐associated lymphoid tissue (MALT) lymphoma in an animal model of ‘Helicobacter heilmannii’ infection

Abstract: While Helicobacter pylori is accepted as the dominant human gastric bacterial pathogen, a small percentage of human infections have been associated with another organism, commonly referred to as 'Helicobacter heilmannii', which is more prevalent in a range of animal species. This latter bacterium has been seen in association with the full spectrum of human gastric diseases including gastritis, peptic ulceration, and gastric carcinomas, including gastric B-cell mucosa-associated lymphoid tissue (MALT) lymphoma.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
76
1
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(82 citation statements)
references
References 24 publications
3
76
1
2
Order By: Relevance
“…The difference between the length of the period before MALT lymphoma occurrence in the study of O'Rourke et al (19) and the length of the period in our study may have been due to differences between the experimental animals and the bacteria used. When the animal species used in the studies are considered, the differences may have resulted from the Th1/2 status of the Th1-predominant C57BL/6 mice and the Th2-predominant BALB/c mice.…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…The difference between the length of the period before MALT lymphoma occurrence in the study of O'Rourke et al (19) and the length of the period in our study may have been due to differences between the experimental animals and the bacteria used. When the animal species used in the studies are considered, the differences may have resulted from the Th1/2 status of the Th1-predominant C57BL/6 mice and the Th2-predominant BALB/c mice.…”
Section: Discussioncontrasting
confidence: 62%
“…In addition, Bcl-X-immunoreactive cells were found in these mice 6 and 12 months later. O'Rourke and colleagues reported finding "Candidatus Helicobacter heilmannii"-associated gastric MALT lymphomas in normal BALB/c mice; furthermore, 15 months after infection with "Candidatus Helicobacter heilmannii"-like isolates from bobcats and other animals, they reported finding lymphoepithelial lesions in up to 80% of the mice, and at 18 months after infection they found lymphomas in up to 25% of the mice (19). The present study clearly demonstrated that "Candidatus Helicobacter heilmannii" infection with cynomolgus monkey mucosal and mucous homogenates resulted in MALT lymphoma formation in 50% of the C57BL/6 mice 3 months after infection and in 100% of the animals 6 months after infection; therefore, this could be a useful animal model of gastric MALT lymphomas, provided that these bacilli can be successfully cultured.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scientists have focused on the essential information that belongs to the bacterium for the last 20 years [8,14,17] . There are evidences on the fact that helicobacter infections cause iron deficiency [11][12][13][14][15][16] .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, O' Rourke et al [8] have managed to distinguish H. felis, H. salomonis, H. bizzozeronii and H. heilmannii by conducting sequence analysis of a part of urease gene complex. In subsequent studies, it has been found out that H. pylori experimentally causes a similar disease in dogs [7] , but Helicobacter is a frequent infection an dogs [9,10] .…”
Section: Introductionmentioning
confidence: 99%